EFEKTIVITAS PROGRAM BPNT TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT KECAMATAN TAMPAN PEKANBARU - Tondhi Ramadhan Ramadhan; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This thesis is proposed to qualify for a Bachelor of Sociology degree. With thetitle "BPNT Program Effectiveness on Welfare Improvement at Tampan DistrictPekanbaru". The problem discussed in this thesis is how the effectiveness of BPNTprogram to improve the welfare of the community in Tampan District. Subjects in thisstudy were 72 people. Sampling technique in this research is Probability samplingtechnique that is sampling technique that gives equal opportunity for every element ofpopulation to be selected become member of sample. The method used descriptivequantitative research methods because this method is more emphasis on aspects ofmeasurement objectively against social phenomena. Data filtering instruments used areobservations, questionnaires, and documents. The theory used is the theory ofeffectiveness, theory of community empowerment and the theory of poverty. Generally,the result of the research is done by the writer can say that with t test of t count =14,000>ttabel = 0.2319, and significance = 0,000 <0,05 then Ha accepted and Horejected, the effectiveness variable of Program BPNT has partially significant influenceto Improvement of People's Welfare.Keywords: BPNT Program, Community, Tampan, Pekanbaru